Ilizarov ring fixator in the management of infected non-unions of tibia - Wani, Naveed Bashir (SICOT J, 2015)
Purpose: The purpose of the study was to evaluate the effectiveness of debridement and application of Ilizarov ring fixator (IRF) in the management of infected tibial non-unions. Patients and methods: Twenty six patients with infected non-unions of tibia were managed by debridement and resection of infected portion ± partial fibulectomy and stabilization by Ilizarov ring fixator. Bone segment transport was done in 18 patients who had greater than 2.5 cm bone defect after debridement. Bone grafting was required in three patients to augment union. Results: All fractures united and infection eradicated completely. There were 13 excellent, nine good, and four fair results. Functional results were excellent in nine, good in 11, fair in five and poor in one. Pin site inflammation was the most common problem and occurred in 23 (88%) patients. There were no major complications or neurovascular complications. Conclusion: We conclude that debridement combined with Ilizarov ring fixator with or without partial fibulectomy is a reliable method of treatment of infected non-unions of tibia.